Human trafficking : interdisciplinary perspectives - Burke, Mary C. (Colección de libros electrónicos de ULoyola, 2013)
The practice of one human being exploiting another in slavery-like conditions is not new. Today, it is called human trafficking. Social, political, and economic forces over the past 60 years have changed how and why this human rights abuse occurs.